Breast cancer metastasis to endometrium: Case report and up-date of literature - Giancarlo Garuti; Paola Francesca Sagrada; Maurizio Mirra; Emilia Marrazzo; Serena Migliaccio; Irene Bonfanti; Marco Soligo (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2023)
Introduction: Breast cancer is the leading neoplasia metastasizing to genital organs. Uterine metastases are seldom reported and those limited to endometrium account for 3.8% of patients with uterine spread. We reported on a woman with breast cancer metastasizing to endometrium and up-date of literature.  Presentation of case: In July 2022, a 59 years-old woman with breast cancer was referred to Gynecological consultation due to Positron Emission Tomography showing an enhanced signal to the endometrium. Throughout the four previous years, she underwent bilateral surgery due to metachronous lobular cancers and adjuvant therapies consisting of Letrozole, Exemestane, chemotherapy, and Tamoxifen. In May 2022, bony metastases were found and she shifted to Abemaciclib/Fulvestrant therapy. No gynecological complaints were recorded, and physical examination was uneventful while Transvaginal Ultrasound demonstrated an enhanced endometrial thickness as a unique abnormality. Hysteroscopy showed mucosal thickenings attributed to Tamoxifen-related cysts formation. The biopsy pathology reported stromal infiltration of neoplastic cells staining for Cytokeratins and GATA-3. Negative staining was reported for PAX-8 and CD-10. On these findings, a breast cancer metastasis was established. Four months later the patients died from metastatic brain progression.  Discussion: Endometrial metastasis from breast cancer is anecdotal. The case described supports that uterine spread is a late event, often concurrent with extragenital metastases and mostly associated with lobular histology. A hysteroscopic view can be misleading and a careful pathological study is needed for a differential diagnosis against endometrial primitiveness.  Conclusion: Endometrial abnormalities in breast cancer patients might be caused by metastasis. The management of these patients is challenging and must be tailored to the clinical background.